Child-Friendly School Management in Improving Children's Welfare at RA Nurul Falah - Ulfadhilah, Khairunnisa; Dwi Nurkhafifah, Salsabila; Ghaitsa Nursyaifa, Bilqis (UIN Siber Syekh Nurjati Cirebon, 2025)
An exploration of the application of child-friendly school management in improving children's welfare at RA Nurul Falah, using a qualitative narrative method. This research prioritizes a humanist perspective by collecting data through interviews, observations, and documentation. A child-friendly school is a concept that emphasizes a safe, fun, and supportive learning environment that supports children's holistic development, both physically, emotionally, and socially. At RA Nurul Falah, inclusive and participatory management is implemented, involving parents, teachers, and the community in the decision-making process. The results of the study show that the improvement of children's welfare can be seen from several aspects, including increased self-confidence, discipline, and children's involvement in various stimulating learning activities. Narratives from parents and teachers revealed significant changes in children's behavior, such as being more open and actively participating in group activities. This is supported by a curriculum that prioritizes the values of character education and child-centered teaching. In addition, healthy environmental factors and decent infrastructure also contribute to creating a conducive learning atmosphere. However, challenges remain, such as the need for ongoing training for educators and limited resources. These findings recommend the need for collaboration from all relevant parties to create sustainable policies and efforts to develop teacher capacity so that child-friendly education can be implemented optimally. In conclusion, the management of child-friendly schools at RA Nurul Falah not only has a positive impact on children's welfare, but also builds a foundation for better child development in the futureKeywords:Child-Friendly, School management, Children’s Welfare